Letters to god series - Norhafsah Hamid (Iman Publication Sdn Bhd, 2022)
Sarah - an introvert and a law student in England, struggling to stay true as a Muslim. Things started to go wrong when Sarah crossed paths with Linda. Everything about Sarah irked Linda, especially her outdated and devout lifestyle. Whilst Sarah endured the backlash from her peers, Jonah - the 'Romeo', came into her life and attempted to woo her like the other women he had charmed. While Sarah endured the nightmare of vicious rumours and being ostracized, Linda was surprised to find herself to be in a somewhat similar situation. Pained and confused, Sarah poured all her grief and sorrow into her letters she wrote to God. Will Sarah find solace through her writings? In this novel, the author brings readers on a journey of rediscovering genuine love and friendship; as well as finding true meaning of serenity in life.